V-OG01 Minimally invasive oesophagectomy: Technique of linear stapled anastomosis. (16th December 2021) - Knight, Benjamin
Abstract: Background: Several anastomotic techniques have been described when performing an oesophagectomy. Each technique has its own merits and drawbacks. The stapled side to side technique creates a widely patent anastomosis with low stricture rate. Methods: This video highlights the technique adopted and developed over the last 5 years. There are several key steps that need to be adhered to, to create a reliable, robust and reproducible anastomosis. These include the orientation of the oesophagus during transection, the use of mucosal retaining sutures, the use of a 34 bougie for the oesophagotomy and the correct retraction of the conduit when performing the anastomosis. Results: The anastomosis was successfully performed without complications. Check endoscopy revealed a widely patent secure join. The anastomosis typically now takes 15–18 minutes. At the end of the procedure, the conduit cap was buried under the pleura and the anastomosis wrapped in omental fat. The patient was discharged on day 10 on a low residue diet. Conclusions: This technique has been adopted and developed over the last 5 years. It has proved reliable and reproducible with a low stricture rate and a very low leak rate. It is easier to perform than a total hand sewn anastomosis and permits visualisation of the luminal oesophagus prior to anastomosis.